COST OPTIMIZATION OF ELECTRICAL ENERGY USED FOR WATER EXTRACTION (Advances in Civil and Architectural Engineering, 2021)
The goal nowadays is to save electrical energy required for water extraction, conditioning and distribution to consumers since it represents the biggest cost in terms of water supply. The topicality of the issue prompted Vodovod-Osijek d.o.o. to analyze the potential electrical energy savings in terms of water extraction and distribution to the city of Osijek. This paper describes water-treatment-related processes along with a comparison of electrical energy consumption with and without a frequency converter.